1976
DOI: 10.1111/j.1550-7408.1976.tb03814.x
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake of Pyrimidine Nucleosides in Tetrahymena. I. Uridine*

Abstract: SYNOPSIS. Uridine uptake was examined in Tetrahymena pyriformis GL‐7 in defined medium under conditions where food vacuole formation is not a significant factor in solute acquisition by the cell. The results indicate the presence of a saturable mechanism which follows Michaelis‐Menten kinetics. When corrected for diffusion the apparent Km for the carrier is 2.3 ± 0.6 μM and the Vmax is 7.3 ± 0.2 × 10−7 nmoles/cell/min. It is evident from nucleotide pool analysis that most of the radioactivity of externally su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Several early studies in T. pyriformis suggested that their transports might involve the use of a nucleoside transporter system [16,25,26]. Transporter proteins in this system have the ability to move one or more types of nucleotides across membranes, with functional redundancies [16,26]. Indeed, results derived from recent bioinformatic analyses suggest that there are more than 10 equilibrative nucleoside transporter genes present in the T. thermophila genome [27,28], indirectly confirming those early observations.…”
Section: The Uptake Of Pyrimidine Bases and Nucleosides In T Thermoph...mentioning
confidence: 63%
See 1 more Smart Citation
“…Several early studies in T. pyriformis suggested that their transports might involve the use of a nucleoside transporter system [16,25,26]. Transporter proteins in this system have the ability to move one or more types of nucleotides across membranes, with functional redundancies [16,26]. Indeed, results derived from recent bioinformatic analyses suggest that there are more than 10 equilibrative nucleoside transporter genes present in the T. thermophila genome [27,28], indirectly confirming those early observations.…”
Section: The Uptake Of Pyrimidine Bases and Nucleosides In T Thermoph...mentioning
confidence: 63%
“…Specifically how nucleobases and nucleosides are transported into Tetrahymena remains unknown. Several early studies in T. pyriformis suggested that their transports might involve the use of a nucleoside transporter system [16,25,26]. Transporter proteins in this system have the ability to move one or more types of nucleotides across membranes, with functional redundancies [16,26].…”
Section: The Uptake Of Pyrimidine Bases and Nucleosides In T Thermoph...mentioning
confidence: 99%
“…pyriformis suggested that the transport of these compounds might involve a nucleoside transporter system [ 16 , 25 , 26 ]. Transporter proteins in this system have the ability to move one or more types of nucleotides across membranes, with functional redundancies [ 16 , 26 ]. Indeed, results derived from recent bioinformatic analyses suggest that there are more than 10 equilibrative nucleoside transporter genes present in the T .…”
Section: Resultsmentioning
confidence: 99%
“…Freeman and Moner fed T . pyriformis GL-7 with [ 3 H]uridine in a short period of time before a new food vacuole could be formed and quantified the amount of radioactive uridine present in different forms in the cell [ 16 ]. They concluded that uridine could enter through the cell surface and was immediately phosphorylated.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors chose short labelling times in order'to be in linear range' of time-dependent pool saturation. The linear range, however, is scarcely observed but assumed to occur between to and the shortest pulse possible (Freemann & Moner, 1976;Wolfe, 1975;Dall'asta et al, 1978). In some instances a background due to incomplete removal of the label is considered and subtracted from the data, with reference to inulin experiments (Reiser & Christiansen, 1972;Winter & Christensen, 1964).…”
Section: Discussionmentioning
confidence: 99%